PERSEPSI KESERIUSAN DAN PERSEPSI HAMBATAN DENGAN TINDAKAN DETEKSI DINI KANKER SERVIKS BERDASARKAN TEORI HEALTH BELIEF MODEL - Kurnia Puji P; Ni Ketut Alit; Retnayu Pradanie (Pediomaternal Nursing Journal, 2014)
Cervical cancer is a serious illness and a leading cause of death in women which needs to be identified as early aspossible. However, most women not really prior about taking early detection due to several problems. Health belief modeltheory is used in this study involves two construction: perceived seriousness and perceived barriers. The purpose of thisstudy was to describe the perceived seriousness and perceived barriers in early detection of cervical cancer based onhealth belief model theory. This study used cross sectional design. The population of this study includes all women in RT03 and RT 06 RW 01 in Kelurahan Mulyorejo Surabaya. The total sample were 106 respondents. The independentvariables in this study were perceived seriousness and perceived barriers in while the dependent variable was the earlydetection of cervical cancer. The data were collected using questionnaires and were analyzed using spearman rhostatistical test in which p = < 0,05. The result shows that perceived seriousness is correlated with the early detection ofcervical cancer (p = 0,006, r = 0,266) and perceived barriers is also correlated with the early detection of cervical cancer(p = 0,000, r = 0,586). Based on the result, it can be concluded that high level of perceived seriousness increase theintention for taking early detection of cervical cancer. On the other hand, high number of perceived barriers lead to lowthat it can intention for taking early detection of cervical cancer. Further research is expected to do more study relatedintervention that can be provided to mothers about the importance of early detection of cervical cancer examination.